Development of Moocs-Assisted Digital Teaching Materials to Increase Student Learning Motivation in the Material of Work and Energy at Bengkulu City High School - Dwi Syafitri, Lola; Risdianto, Eko; Medriati, Rosane (Tadbir : Jurnal Studi Manajemen Pendidikan, 2024)
The aim of this research is to produce a product in the form of digital teaching materials assisted by MOOCs to increase students' motivation in learning about effort and energy. Research is also useful for looking at the increase in student motivation between before and after using MOOCs-assisted digital teaching materials on effort and energy as well as seeing the link between motivation and learning outcomes. The research method used is the R&D research method using the 4D model. The instruments used in this study were questionnaires, observations, interviews. This research uses the methodpra eksperimental one grup pretes posttes design. This research was tested on a limited basis in one of class X at SMAN 9 Bengkulu City. The results obtained are that students feel more motivated when learning to use digital teaching materials assisted by MOOCs. This is in accordance with the results of the perception questionnaire which obtained 84.87% containing suggestions and stating that MOOCs-assisted digital teaching materials were very interesting. The results of the pre-test and post-test conducted also prove that there is a link between learning motivation and learning outcomes where the average student can increase from 55 to 93.8.p